Barriers and Facilitators To Patient-Centered Care In Nursing Leadership Practice: A Systematic Review - Matsum, Iwan; Maelani, Ina; Hapsari, Shindi (ProNers, 2025)
Background: Patient-centered care (PCC) represents the gold standard in healthcare delivery. Nursing leadership plays a critical role in implementing PCC; however, organizational barriers remain insufficiently explored. Methods: This systematic review employed the SPIDER framework (Sample, Phenomenon of Interest, Design, Evaluation, Research Type). Academic databases searched included PubMed, ScienceDirect, and Google Scholar, with articles published between 2020 and 2025. Results: Three key themes emerged from the analysis. The first theme encompasses barriers, including toxic leadership (57%), rigid hierarchical structures (50%), and high workloads (63%). The second theme relates to facilitating factors, consisting of transformational leadership (79%) and interprofessional collaboration (86%). The third theme involves technological support, reflected in the utilization of Electronic Health Records (EHR) and digital feedback tools (71%). Conclusion: Transforming nursing leadership to support PCC requires deconstructing hierarchical structures, strategic resource allocation, and implementing simulation-based communication training.